Testosterone replacement therapy reduces biochemical recurrence after radical prostatectomy. (1st April 2020) - Ahlering, Thomas E.; My Huynh, Linda; Towe, Maxwell; See, Kaelyn; Tran, Joshua; Osann, Kathryn; el Khatib, Farouk M.; Yafi, Faysal A.
Abstract : Objective: To evaluate risk of prostate cancer biochemical recurrence (BCR) after radical prostatectomy (RP) in men receiving vs not receiving testosterone replacement therapy (TRT). Patients and Methods: A total of 850 patients underwent RP by a single surgeon. All patients had preoperative testosterone and sex hormone‐binding globulin levels determined; free testosterone was calculated prospectively. In all, 152 (18%) patients with low preoperative calculated free testosterone (cFT) levels and delayed postoperative sexual function recovery were placed on TRT and proportionately matched to 419 control patients by pathological Gleason Grade Group (GGG) and stage. Rates and time to BCR [two consecutive prostate‐specific antigen (PSA) levels of ≥0.2 ng/mL] were compared in univariate and multivariate regression; Cox regression was used to generate a survival function at the mean of covariates. Results: The median follow‐up was 3.5 years. There were no statistically significant differences in demographics or general health complications between groups. BCR occurred in 11/152 (7.2%) and 53/419 (12.6%) patients in the TRT and control groups, respectively. In adjusted time‐to‐event analysis, TRT was an independent predictor of recurrence‐free survival. After accounting for GGG, pathological stage, preoperative PSA level, and cFT, patients on TRT were 54% less likely to recur (hazard ratio 0.54, 95% confidence interval 0.292–0.997). In men destined to recur, TRT delayed time to recurrence by an average of 1.5 years. Conclusion: In our experience, TRT after RP significantly reduced BCR and delayed time to BCR. There was no identifiable general health complications associated with TRT. These findings are hypothesis‐generating and require confirmation with multi‐centred, prospective randomised controlled trials.